2018
DOI: 10.1111/sji.12697
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mimicry: An explanation for autoimmune diseases and infertility

Abstract: Microorganisms execute an enthralling range of adjustments in order to survive in the host. Among the various strategies employed by microorganisms to surmount the host immune response, the phenomenon of molecular mimicry empowers the microorganisms to manoeuvre host physiology and cellular functions for their own advantage by mimicking the host proteins and initiating autoimmunity. This phenomena, by and large, has been studied in context of autoimmune diseases, however, its implications have also been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 91 publications
(133 reference statements)
0
17
1
Order By: Relevance
“…Although the duration of infertility and the type of infertility increase the risk of STDs by increasing risky sexual behavior [42] [43] [44] and STDs are responsible for the production of ASA by antigenic community with the spermatozoa or by destruction of the blood-testicular barrier [45] [46], we found no association between the duration of infertility in men and ACAS positivity. Unlike us, Tennakoon V [47] found the association.…”
Section: Discussioncontrasting
confidence: 62%
“…Although the duration of infertility and the type of infertility increase the risk of STDs by increasing risky sexual behavior [42] [43] [44] and STDs are responsible for the production of ASA by antigenic community with the spermatozoa or by destruction of the blood-testicular barrier [45] [46], we found no association between the duration of infertility in men and ACAS positivity. Unlike us, Tennakoon V [47] found the association.…”
Section: Discussioncontrasting
confidence: 62%
“…To date, different molecular mechanisms have been reported to play a role in autoimmune processes, such as pathogen/host interaction, and molecular mimicry [ 52 , 53 ]. Moreover, it has also been shown that cross-reactive Abs produced in the context of microbial infections have the potential to cause damage to host tissues [ 54 , 55 ].…”
Section: Ra Immunopathogenesismentioning
confidence: 99%
“…The immune reaction in spermatozoa causes 2-30% of infertility (34) and in 9-12.8% of infertile couples were found anti-sperm antibodies (35,36). Affected women of bacterial vaginitis caused by Staphylococcus aureus develop antibodies against S. aureus that cross-react with human spermatozoa proteins which could be a potential cause of infertility (37). A molecular modeling approach revealed 55 of 96 human spermatozoa proteins with homology to S. aureus proteins (identity 19-45%).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%